Chinese Herbal Products for Non-Motor Symptoms of Parkinson’s Disease in Taiwan: A Population-Based Study - Lin, Chien-Hung; Chiu, Hsienhsueh Elley; Wu, Szu-Ying; Tseng, Shih-Ting; Wu, Tzu-Chan; Hung, Yu-Chiang; Hsu, Chung Y.; Chen, Hsuan-Ju; Hsu, Sheng-Feng; Kuo, Chun-En; Hu, Wen-Long (Frontiers in Pharmacology, 2021)
Objective: Combinations of Chinese herbal products (CHPs) are widely used for Parkinson’s disease (PD) in Taiwan. Thereby, we investigated the use of CHPs in patients with PD. Methods: This study was a population-based cohort study that analyzed the data of patients with PD from the National Health Insurance Research Database. A total of 9,117 patients were selected from a random sample of one million individuals included in this database. We used multiple logistic regression models to estimate the adjusted odds ratios of the demographic factors and analyzed the formula and single CHPs commonly used for PD. Results: Traditional Chinese medicine users were more commonly female, younger, of white-collar status, and residents of Central Taiwan. Chaihu-Jia-Longgu-Muli-Tang was the most commonly used formula, followed by Ma-Zi-Ren-Wan and then Shao-Yao-Gan-Cao-Tang. The most commonly used single herb was Uncaria tomentosa (Willd. ex Schult.) DC., followed by Gastrodia elata Blume and then Radix et Rhizoma Rhei (Rheum palmatum L., Rheum tanguticum Maxim. ex Balf., and Rheum officinale Baill.). Chaihu-Jia-Longgu-Muli-Tang and U. tomentosa (Willd. ex Schult.) DC. have shown neuroprotective effects in previous studies, and they have been used for managing non-motor symptoms of PD. Conclusion: Chaihu-Jia-Longgu-Muli-Tang and U. tomentosa (Willd. ex Schult.) DC. are the most commonly used CHPs for PD in Taiwan. Our results revealed the preferences in medication prescriptions for PD. Further studies are warranted to determine the effectiveness of these CHPs for ameliorating the various symptoms of PD, their adverse effects, and the mechanisms underlying their associated neuroprotective effects.